Antidepressant, neuropharmacological activity and mode of action of theaflavin-3-gallate in in vitro and in vivo models of depression - Ying Wang; Jing Chen; Jing Wang; Xin Guo; Ning Wang; Jie Yuan (Bangladesh Pharmacological Society, 2018)
Herein the antidepressant-like effect of theaflavin-3-gallate, a plant polyphenolic compound in 1-methyl-4-phenyl pyridinium-induced neuronal injury in N2a cells used as an in vitro model of depression as well as in vivo. The results from MTT (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide) and lactic dehydrogenase assay revealed that theaflavin-3-gallate exerted a neuroprotective effect in N2a cells. Treatments with mixtures of 1-methyl-4-phenyl pyridinium (20 µM) and four concentration levels of theaflavin-3-gallate increased cell viability from 23.3 to 79.6% while lactic dehydrogenase leakage value decreased from 63.2 to 23.4 U/L. Fura-2-acetoxymethyl ester assay for Ca2+ concentration measurement revealed that different doses of theaflavin-3-gallate or fluoxetine (20 µM) reduced the intracellular Ca2+ overloading in N2a cells induced by 1-methyl-4-phenyl pyridinium. Inverted phase microscopy showed that theaflavin-3-gallate induced neurite outgrowth in 1-methyl-4-phenyl pyridinium-induced neurotoxicity in N2a cells. Theaflavin-3-gallate could significantly reduce the immobility time of mice in both forced swimming test and tail suspension test. Video Clip of Methodology: MTT Assay: 3 min 38 sec   Full Screen   Alternate